Implementasi Fatwa Dsn-Mui No: 107/Dsn-Mui/X/2016 Tentang Pedoman Penyelenggaraan Rumah Sakit Berdasarkan Prinsip Syariah Di Rumah Sakit Qolbu Insan Mulia Batang - Tsaury, Assilmi Kaffatan Ats; Kholil, Makrum (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
A hospital can be categorized as a sharia hospital if it is in accordance with DSN-MUI Fatwa No: 107/DSN-MUI/X/2016 concerning Guidelines for Hospital Operations Based on Sharia Principles as a reference. DSN MUI Fatwa No. 107/DSN-MUI/X/2016 on October 01, 2016 has set the conditions that must be met by every hospital that uses a Sharia-based system. So there is a difference between a General Hospital (RSU) and a Sharia Hospital. Recently, many hospitals have implemented sharia principles, especially in the aspect of their services, one of which is the Qolbu Insan Mulia Batang General Hospital. Therefore, this study aims to analyze and describe the implementation of the DSN-MUI Fatwa No: 107/DSN-MUI/X/2016 at Qolbu Insan Mulia Batang Hospital whether the service aspect is in accordance with the DSN-MUI Fatwa No: 107/DSN- MUI/X/2016. This type of research is a field research using a qualitative approach. Determination of research informants using purposive sampling technique, the authors apply several criteria or conditions in determining research subjects. The data analysis used descriptive qualitative. Based on the results of the study, it can be seen that the management system of the Qolbu Insan Mulia Batang RSU in applying sharia principles which include contracts, services, drugs, food and beverages and fund management is not fully in accordance with the DSN-MUI fatwa no. 107/DSN-MUI/X//2016.